2011
DOI: 10.1007/s11255-011-9977-y
|View full text |Cite
|
Sign up to set email alerts
|

Body composition monitor measurement technique for the detection of volume status in peritoneal dialysis patients: the effect of abdominal fullness

Abstract: BIS is a reliable method to evaluate volume status in PD patients. BIS performed after peritoneal equilibration test with an empty abdomen, better reflects overhydration and is related to echocardiographic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Using a sensitive 8 electrode MF-BIS device [21] there were differences in TBW, ICW and ECW recorded, whereas other studies using 4 electrode devices have not demonstrated a difference [22]. The changes in ECW and ICW were less than that in total body weight, with proportionately greater change in ECW.…”
Section: Discussionmentioning
confidence: 84%
“…Using a sensitive 8 electrode MF-BIS device [21] there were differences in TBW, ICW and ECW recorded, whereas other studies using 4 electrode devices have not demonstrated a difference [22]. The changes in ECW and ICW were less than that in total body weight, with proportionately greater change in ECW.…”
Section: Discussionmentioning
confidence: 84%
“…Compound 21 $ PD123319 .. AngIV . Ang (1-7) in the AT 2 receptor-transfected HEK-293 cells (Jones et al, 2011;Sipahi et al, 2011). Shorter angiotensin peptides may act as endogenous ligands at the AT 2 receptor; therefore, defining the physiology as well as the concept of separate receptors for AngII-metabolite peptides should formally rule out AT 2 receptor-mediated effects.…”
Section: B Pharmacologymentioning
confidence: 99%
“…27,28 Sipahi et al 29 found BIS findings to be related with echocardiographic findings of OH in PD patients.…”
Section: Discussionmentioning
confidence: 95%